2017
DOI: 10.1177/1362361317699584
|View full text |Cite
|
Sign up to set email alerts
|

Supporting university students with autism spectrum disorder

Abstract: Increasing numbers of students with autism spectrum disorder are entering higher education. Their success can be jeopardized by organizational, social/emotional, and academic challenges if appropriate supports are not in place. Our objective was to evaluate the effectiveness of a support group model for university students with autism spectrum disorder in improving psychological and functional outcomes. A curriculum guided the weekly discussions and consisted of topics such as time and stress management, manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 36 publications
4
81
0
5
Order By: Relevance
“…Just like in the Stepped Transition in Education Program for Students with ASD (STEPS; White et al 2017) EF can possibly be improved by teaching effective problem-solving and goalsetting skills. Additionally, according to Hillier et al (2018), support groups with fellow ASD students, consisting of weekly meetings addressing common challenges experienced by students in university settings, enhance success for students with autism. The participants reported for example an increase in behaviors like implementing strategies to reduce stress and anxiety and learning how to set and meet appropriate goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Just like in the Stepped Transition in Education Program for Students with ASD (STEPS; White et al 2017) EF can possibly be improved by teaching effective problem-solving and goalsetting skills. Additionally, according to Hillier et al (2018), support groups with fellow ASD students, consisting of weekly meetings addressing common challenges experienced by students in university settings, enhance success for students with autism. The participants reported for example an increase in behaviors like implementing strategies to reduce stress and anxiety and learning how to set and meet appropriate goals.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, individuals with ASD with moderate to high intelligence are likely to follow postsecondary education including college and university programs. Based on findings in the USA it is assumed that between 0.7 and 1.9% of young adults without concurrent intellectual disability meet criteria for autism (White et al 2011), and numbers are reported to be increasing (Hillier et al 2018) in the US with 46% since 2000 (Shmulsky et al 2017). As students in higher education are not required to inform the institute about their diagnosis, exact numbers of students with autism in higher education are not available.…”
mentioning
confidence: 99%
“…On the other hand, the procedures that we derived from Stocco et al () may not be appropriate for some students with diagnosed disabilities. Due to growing numbers of individuals with a diagnosis of ASD entering higher education (Hillier et al, ), more research is needed on teaching interview skills to college students with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Even though prior research demonstrates a clear need for programming to help autistic college students transition into and succeed in college (Glennon, 2001 ; Adreon and Durocher, 2007 ; Hendricks and Wehman, 2009 ; Kapp et al, 2011 ; Pillay and Bhat, 2012 ; Gobbo and Shmulsky, 2014 ) and the Interagency Autism Coordinating Committee ( 2013 ) identified transition programming for autistic adults as a priority, only a very small body of research has provided preliminary evidence that supports for incoming and current autistic college students are attractive to and/or beneficial for them (Pugliese and White, 2014 ; Schindler et al, 2015 ; Ames et al, 2016 ; Barnhill, 2016 ; White et al, 2016a , 2017 ; Gillespie-Lynch et al, 2017a , b ; Roberts and Birmingham, 2017 ; Hillier et al, 2018 ). As an early example of this type of work, Pugliese and White ( 2014 ) demonstrated the feasibility and acceptability of a cognitive-behavioral group-based problem solving skills intervention for five autistic college students.…”
Section: Introductionmentioning
confidence: 99%